ASSESMENTPSIKOLOGI WARGA BINAAN DALAM MENGHADAPI PERSIAPAN MASA BEBAS PADA NARAPIDANA DI LEMBAGA PEMASYARAKATAN - Ary Wicaksono, David; Mariska Aryono, Marcella (Widya Warta, 2020)
This  study  aims  to  determine  the  psychological  condition  of  the  prisoners  who  are  in  the process  of  leaving  the  prison.  The  subjects  of  this  study  were  eight participants.  Data collection methods in this study were observation, interviews and several psychological tests. Data analysis in this study employed descriptive analysis in which the research was intended to provide a complete picture of the social setting of how individuals were prepared to interact with  the  community.  The  results  of  this  study  show  that  the  psychological  conditions  of  the prisoners  who  are  in  the  process  of  leaving  the  prison  are  quite  ready  to  return  to  the community,  although  there  are  still  many  things  that  require  improvement  in  order  to  be better prepared when returning to society.